Fecal MicroRNAs as Potential Biomarkers for Screening and Diagnosis of Intestinal Diseases - Rashid, Humaira; Hossain, Biplob; Siddiqua, Towfida; Kabir, Mamun; Noor, Zannatun; Ahmed, Mamun; Haque, Rashidul (Frontiers in Molecular Biosciences, 2020)
MicroRNAs (miRNAs) are a class of conserved endogenous, small non-coding RNA molecules with length 18-25 nucleotides that regulate gene expression by RNA interference processes, including mRNA chopping, mRNA deadenylation and translation inhibition. miRNAs maintain the physiological functions of the intestine and are instrumental in gut pathogenesis. miRNAs play an important role in intercellular communication and are present in all body fluids, including stools with different composition and concentrations. However, under diseased condition miRNAs are aberrantly expressed and act as negative regulators of gene expression. The stable and differentially expressed miRNAs in stool enables miRNAs to be used as potential biomarkers for screening of various intestinal diseases. In this review, we summarize the expressed miRNA profile in stool and highlight miRNAs as biomarkers with potential clinical and diagnostic applications, and we aim to address the prospects for recent advanced techniques for screening miRNA in diagnosis and prognosis of intestinal disorders.